Lilium liangiae, a new species in the genus Lilium (Liliaceae) that reveals parallel evolution within morphology - Yuan, Yumei; Gao, Yundong (Frontiers in Plant Science, 2024)
The former genus Nomocharis, which been merged as a clade within the genus Lilium (Liliaceae) represents one of the most complicated and unclear groups included in the latter. Research on members of the Nomocharis clade has been quite limited due to the sampling difficulties caused by its selective environmental preferences. In this study, we propose a new species within this clade, L. liangiae, as a further bridge connecting the former genus Nomocharis with other members of the genus Lilium. The clustering results of 38 morphological traits indicated that the new species is allied to Nomocharis, further increasing the morphological polymorphism in the latter. Through phylogenetic analysis, comparative genomic analysis of nuclear internal spacers and the newly generated complete chloroplast genome, in conjunction with previously published sequences, the phyletic results and morphological clustering both supported L. liangiae belonging to subclade Ecristata in Nomocharis, its closest affinity being L. gongshanense. Inconsistencies in phylogenetic relationships were detected between nuclear and plastid datasets, possibly due to ancient hybridization and ongoing introgression. Comparative genomics revealed the conservation and similarity of their chloroplast genomes, with variations observed in the expansion and contraction of the IR regions. A/T and palindromic repeat sequences were the most abundant. Seven highly variable regions (Pi≥0.015) were identified as potential molecular markers based on the chloroplast genomes of 47 species within Lilium. Both nuclear and plastid genes exhibited very low variability within the Nomocharis clade, this contrasting with their highly variable morphological appearance. When considering the ancestral state reconstruction analysis, it appears that the campanulate flower form, as in L. liangiae, arose at least three times within the genus Lilium, revealing parallel evolution in the latter. Overall, this study adds important genetic and morphological evidence for understanding the phylogenetic relationships and parallel evolution pattern of species within the genus Lilium.